1994
DOI: 10.1161/01.cir.90.1.362
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II increases plasminogen activator inhibitor type 1 and tissue-type plasminogen activator messenger RNA in cultured rat aortic smooth muscle cells.

Abstract: Recent research has demonstrated the existence of a localized vascular renin-angiotensin system. The finding that Ang II can potentially modulate the plasminogen activation in the arterial wall has important biological and therapeutical implications for the evolution of arterial wall thrombi and the migration of cells through the vessel wall in the genesis of atherosclerotic lesions. We speculate that the reduction in thrombotic events observed in patients with a previous myocardial infarction and in high-reni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
2
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(87 citation statements)
references
References 49 publications
8
74
2
2
Order By: Relevance
“…Previous reports have shown that the vasopressive peptide Ang II is a potent stimulator of PAI-1 expression in both vascular endothelial and SMCs 23,24,51 and that angiotensinconverting enzyme (ACE) inhibition reduces both vascular and plasma PAI-1 levels. 18,52 These reports suggest that the renin-angiotensin system, via the actions of Ang II, can contribute to the expression of PAI-1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have shown that the vasopressive peptide Ang II is a potent stimulator of PAI-1 expression in both vascular endothelial and SMCs 23,24,51 and that angiotensinconverting enzyme (ACE) inhibition reduces both vascular and plasma PAI-1 levels. 18,52 These reports suggest that the renin-angiotensin system, via the actions of Ang II, can contribute to the expression of PAI-1.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Control cells and cells pretreated with natriuretic factors for 5 minutes were stimulated with either Ang II or PDGF for 3 hours. Northern blot analyses of both PAI-1 and acidic ribosomal phosphoprotein PO mRNA (36B4, a constitutively expressed mRNA) were performed as described previously.…”
Section: Effect Of Natriuretic Peptides On Pai-1 Mrna Expression In Rmentioning
confidence: 99%
See 1 more Smart Citation
“…112 Conflicting data suggest that losartan may mediate antifibrinolytic activity via reduction of PAI-1 expression and activity, 113-117 and other reports suggest that losartan may inhibit fibrinolysis by alternate actions through prevention of platelet aggregation (Figure 3). 118,119 The different observations about PAI-1 activity and expression may reflect the manner in which the analyses were conducted, such as timing of sample collection and duration of treatment, u3 Reduction of PAI-1 levels by candesartan, valsartan, and irbesartan would, however, suggest that All-mediated inhibition of fibrinolysis may be affected by the AT 1 receptor.…”
Section: Thrombosismentioning
confidence: 98%
“…Although mean cortisol concentration was higher during low salt intake than during high salt intake and serum cortisol concentration increased with the number of PAI-1 4G alleles under high-salt conditions, there was no correlation between cortisol and PAI-1 antigen under either low-or high-salt conditions. Both Ang II (or its hexapeptide metabolite, Ang IV) and aldosterone increase PAI-1 expression in a variety of cell types, including astrocytes, 35 endothelial cells, 4 vascular smooth muscle cells, 36 proximal tubular epithelial cells, 37 and mesangial cells. 38 Systemic infusion of Ang II increases vascular, renal, and hepatic PAI-1 expression in rats, 39 whereas treatment of animals with ACE inhibitors, AT 1 receptor antagonists, or aldosterone receptor antagonists decreases tissue PAI-1 expression.…”
Section: Discussionmentioning
confidence: 99%